"You Can Make a Difference": Teachers’ Agency in Addressing Social Differences in the Student Body - Behrmann, Laura (Social Inclusion, 2021)
Teachers are key players in transforming the education system (van der Heijden et al., 2015). They shape educational processes, influence school policies, and make day‐to‐day decisions that have a direct effect on students (Vähäsantanen, 2015). Yet we currently know very little about whether they can contribute to the creation of social equality of opportunity. This article focuses by way of example on the experiences and interpretative schemes of teachers in Germany, as the country is known for its highly selective school system. It draws on data from an exploratory study based on 20 narrative interviews (Rosenthal, 2018) with schoolteachers at three comprehensive schools in East and West Germany, which were selected because comprehensive schools in Germany see themselves as a more equal‐opportunity form of education. The article begins by identifying four types of teacher action orientations in addressing the social differences of schoolchildren. Unexpectedly, only a few teachers exhibited a socially conscious inclination to act—for example, by providing targeted support to schoolchildren from socially disadvantaged households. In the second step, by comparing teacher biographies, school environments, and historical imprints, the article attempts to identify certain conditions under which teachers perceive themselves as responsible for addressing social differences among students. Beyond illustrating the interplay of biographical experiences and school culture, the study’s east-west contextualization opens up a new perspective for examining the lingering implications of the German half‐day schooling model even after the introduction of all‐day schooling in 2003. One possible conclusion is that the transformation of the German school system from a half‐day to an all‐day model has not taken the tasks of teachers into account, which, as this article points out, would be important in making them aware of schoolchildren’s different social backgrounds and their effects on achievement.